Participation à la conférence de l’ACFAS sur les femmes officielles des communautés linguistiques minoritaires à Ottawa - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Attending the ACFAS Official Women Minority Language Communities Conference in Ottawa - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Les femmes dans les communautés de langue officielle en situation minoritaire - Quebec English-speaking Communities Research Network (QUESCREN); Canadian Institute for Research on Linguistic Minorities (2024)

Women in Official Language Minority Communities - Quebec English-speaking Communities Research Network (QUESCREN); Canadian Institute for Research on Linguistic Minorities (2024)
Keywords: Official Language Minority Community (OLMC)

Access to Justice in English Project : Senior Care Services in English in Quebec : Executive Summary of Final Report and Recommendations to the Ministry of Health and Social Services - Quebec Community Groups Network (QCGN) (2023)

ARC Mental Health Information Series : D-MER Dysphoric Milk Ejection Reflex - Assistance and Referral Centre (ARC) (2023)

ARC Mental Health Information Series : Eating Disorders - Assistance and Referral Centre (ARC) (2023)

ARC Mental Health Information Series : Perimenopausal Depression - Assistance and Referral Centre (ARC) (2023)

ARC Mental Health Information Series : Perinatal Loss and Grief - Assistance and Referral Centre (ARC) (2023)

ARC Mental Health Information Series : PMDD- Premenstrual Dysphoric Disorder - Assistance and Referral Centre (ARC) (2023)

ARC Mental Health Information Series : Postpartum Anxiety - Assistance and Referral Centre (ARC) (2023)

ARC Mental Health Information Series : Postpartum Depression - Assistance and Referral Centre (ARC) (2023)

ARC Mental Health Information Series : Substance Use Disorder in Women - Assistance and Referral Centre (ARC) (2023)

Money Raised for La Rose des Vents de Drummond and a Successful First Edition of the “History and Music” Concert Series - Centre for Access to Services in English (CASE) (2022)

Window Onto Local Farming : Être femme en agriculture / Women in Agriculture - Miller, Julie; Lapierre, Carole-Anne (2021)

Report on the Proceedings of the Advancing Women in STEM Community Leaders Forum & Strategic Recommendations - Association for Canadian Studies (ACS) (Youth Employment Services (YES), 2018)
YES Montreal is currently leading one of 20 initiatives funded by Status of Women to advance gender equality in Canada. Advancing Women in STEM is a three-year grant project (2017-2020) that aims to address and identify solutions to a number of systemic challenges hindering women’s retention and access to leadership positions within the STEM industry. This initiative follows from two previous ones; in the inaugural project (2012-2015), YES conducted three annual gender-based analyses of Quebec’s technology sector and in the second project (2015-2017) developed a tailored mentorship model for women in Montreal’s STEM industry. The overarching goal of the Advancing Women in STEM project is to create systemic change within STEM companies by shifting institutional practices to promote inclusivity and leadership opportunities for women. Successfully achieving this goal is dependent on the collaboration and support of industry and community leaders, particularly the project’s advisory committee that consists of fifteen outstanding women leaders who are highly engaged in this initiative and its outcomes.

Women in the STEM Sector - Jedwab, Jack (2016)
Gender-based analysis (hereafter GBA) is defined by Status of Women Canada “a method for examining how an issue is affected by sex, gender, and other intersecting identity factors. It involves examining disaggregated data, as well as social, economic, and cultural conditions and norms.” (GBA: Gender-Based Analysis Plus, SWC 2015). The goal of this project is to conduct a gender-based analysis of the barriers and opportunities faced by women in the Science, Technology, Engineering and Math sector (hereafter STEM), notably when it comes to advancement in their careers. GBA uses sex and gender as entry points to examining an issue, while situating these factors across various identities and experiences. In this report, we focus on the STEM sector, a highly educated group of women from diverse backgrounds, in the Montreal area. We examine this group in relationship to the broader community, as well as focusing on differences across this group, namely in terms of experience within the field.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Estrie – CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Gaspésie - Pocock, Joanne (2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Montérégie-Est - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS des Îles - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS du Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS du Centre-Sud-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2 : English-speaking Women and Mothers : RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2 : English-speaking Women and Mothers : RTS du Saguenay – Lac-Saint-Jean - Pocock, Joanne (The Community Health and Social Services Network, 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Profile communautaire jeunes et aînés : Populations anglophones Gaspé - Vision Gaspé-Percé Now (2016)
Ce document est une ressource pour les organismes communautaires et gouvernementaux et pour ceux qui peuvent bénéficier de l’information visant les aînés et les jeunes anglophones de Gaspé. La production du document est possible grâce au soutien financier de Santé Canada. Les données démographiques ont été fournies par le Réseau communautaire de santé et des services sociaux (RCSSS).

Consultation générale et auditions publiques sur le projet de loi n° 60 - The English Speaking Catholic Council (ESCC) (2013)
Le Conseil catholique d'expression anglaise (CCEA) s’oppose à la charte proposée par le projet de loi 60, et ce, pour les raisons suivantes : • Il menace d’éroder, d’un point de vue historique et juridique, les libertés fondamentales de conscience, de religion, d’opinion et d’expression. Il s’agit des libertés « primordiales » dans notre société et il faut s’opposer à tout ce qui tend à diluer ou à réduire ces libertés. • Il propose une société sécularisée dans laquelle l’expression et la pratique religieuses sont marginalisées. Il cherche à recadrer le débat public de manière à ce que l’exercice des droits et libertés protégés par les chartes soit perçu comme imposé à la société et nécessitant la permission de l’État. • Il formule une notion embrouillée de la séparation de l’Église et de l’État en proposant que l’État a le pouvoir de définir la nature des croyances, de la pratique et de l’expression religieuses. • Dans tous les points susmentionnés, il situe le rôle de l’État au-dessus des paramètres de gouvernance appropriés d’un gouvernement élu démocratiquement et responsable. Le CCEA demande au gouvernement du Québec de retirer le projet de loi 60.

General Consultation and Public Hearings on Bill 60 - The English Speaking Catholic Council (ESCC) (2013)
The English Speaking Catholic Council (ESCC) objects to the proposed “Charter,” Bill 60, on the following grounds: • It threatens to erode the historically and legislatively foundational freedoms of conscience, religion, opinion and expression. These are considered to be “first” freedoms in our society and any trend to dilute or undermine these freedoms must be resisted. • It proposes a secularized society in which religious expression and practice are marginalized. It seeks to reframe the public discussion so that the exercising of Charter-protected rights is to be understood as an imposition upon society which requires the permission of the State. • It muddies the separation of Church and State as it proposes the State has the power to define the nature of religious belief, practice and expression. • In all of the aforementioned points the role of the State is elevated above the proper parameters of a democratically elected and responsible government. The ESCC calls upon the Government of Quebec to withdraw Bill 60.

A Response to Bill 60 : Charter Affirming the Values of State Secularism and Religious Neutrality and of Equality Between Women and Men, and Providing a Framework for Accommodation Requests - Quebec Federation of Home and School Associations (QFHSA) (Quebec Federation of Home and School Associations (QFHSA), 2013)
Brief sent to The Committee on Institutions. The Quebec Federation of Home and School Associations Inc. (QFHSA) would like to thank the Committee on Institutions for the opportunity to respond to Bill 60. This Bill was studied in detail by the Rights Committee and the response of the Federation was passed by the Board of Directors on behalf of the membership. QFHSA is opposed, in its entirety, to Bill 60, a Charter affirming the values of State secularism and religious neutrality and of equality between women and men, and providing a framework for accommodation requests.

Gender-based Approach to Women in Technology Project: Women in Technology : Final Report - Wood, Andrea (2013)
This paper represents the research component of a larger project focusing on “women in technology”, an initiative launched by YES Montreal in autumn 2012. The project strives to build capacity in Montreal’s technology sector by applying a gender-based analysis in the advocacy of women’s career development in the technology sector. The research will support the delivery of programs focusing on the development, implementation and evaluation of women’s careers in technology over a 3-year period, between 2013 and 2015.

Women in Technology - Wood, Andrea (Youth Employment Services (YES), 2013)
This paper represents the research component of a larger project focusing on “women in technology”, an initiative launched by YES Montreal in autumn 2012. The project strives to build capacity in Montreal’s technology sector by applying a gender-based analysis in the advocacy of women’s career development in the technology sector. The research will support the delivery of programs focusing on the development, implementation and evaluation of women’s careers in technology over a 3-year period, between 2013 and 2015. The Montreal technology sector faces a pipeline issue. This report aims to improve the understanding of the factors influencing the technology sector’s lifecycle, from elements impacting early technology education through career development. Predominantly, the research addresses the issues that prevent women in Quebec’s technology sector from achieving their goals. In order to elaborate upon the issues and opportunities, the study relies on two forms of research: secondary research conducted by experts in the field, and primary data collected through surveys, focus groups and interviews.

Ladies' Protestant Home 1859-2009 : 150 Years of History - Donovan, Patrick; Hayes, Ashli (2009)
This is the story of how, for the past 150 years, English-speakers in Quebec saw needs in the community and reached out to meet them. The Ladies’ Protestant Home was founded in 1859, a time when epidemics, poor work conditions, and frequent urban fires made life difficult for the poor. There was a crying need for institutions to help out. In its early years, the Home provided temporary shelter for poor and destitute Protestant immigrant women. Its mandate evolved over the years, with an increasing focus on serving the elderly from the 1950’s onward. The Home eventually reached out to non-Protestants, Francophones, and men before closing down in 1990. For the past two decades, the Quebec Ladies’ Home Foundation has continued to manage assets from the Home's sale towards the purpose of providing health and social services to English-speakers in Quebec City.

Semaji - Black Community Resource Centre (BCRC) (2008)

A Study of Women's Needs on the Lower North Shore - Keats, Shannon A. (Coasters Association, 2006)
The mission of the Coasters Association is to develop knowledge of the needs and expectations of the fourteen (14) communities on the Lower North Shore, and act in partnership with community leaders, organizations and stakeholders to design and deliver community strategies, programs and services which respond to the region’s development challenges. In keeping with their mission and providing an opportunity to better the situation of women on the Lower North Shore, a project entitled “A Study of the Needs of Women on the Lower North Shore”, was initiated. The project began on the September 12th, 2005 and ended on March 31st, 2006 (29 weeks). The key goal of the project was to get women involved and talk about the issues facing them and to identify opportunities and lasting solutions, as well as make women aware of the programs and services that are available on the coast, through partnerships with other organizations and to help these women make use of those programs. The purpose of the project was to research information through means of a questionnaire and by organizing focus groups to develop a needs assessment and to establish a coalition (for Phase 2 of the project) to improve the overall status of women on the Lower North Shore of Quebec.

Alliance Quebec Denounces an Alarmist La Presse Story - Alliance Quebec (AQ) (1999)

ARC Mental Health Information Series : Prenatal Depression - Assistance and Referral Centre (ARC)

Qui suis-je? / Who am I? - Centre for Access to Services in English (CASE)